Collective action in invasive species control, and prospects for community-based governance: The case of serrated tussock (Nassella trichotoma) in New South Wales, Australia. (November 2016) - Marshall, Graham R.; Coleman, Michael J.; Sindel, Brian M.; Reeve, Ian J.; Berney, Peter J.
Highlights: Community-based, polycentric governance of invasive species control has potential to be more effective than traditional government-centred approaches. Research was conducted to explore this potential with respect to the invasive weed Nassella trichotoma in New South Wales, Australia. Lack of effective collective action is a more significant barrier to effective control of this species than lack of information. Landholders are willing to participate in community-based serrated tussock management to improve the collective response to this problem. Such an approach is feasible, and should complement rather than replace existing serrated tussock management approaches. Abstract: Responsibility for solving collective action problems in invasive species control has conventionally been assigned to government. The large continuing costs arising from invasive species demonstrate the limitations of government-centred (monocentric) approaches to governance in this domain, and indicate a need for polycentric alternatives which complement government capacities with those of landholders and their community organisations. We sought to add to existing knowledge about collective action problems for invasive species management, and to explore the potential for community-based, polycentric approaches to improve management in this domain, through workshops and a survey of landholders regarding the weed serrated tussock ( Nassella trichotoma ) in two regions of New South Wales, Australia. Serrated tussock threatens the private interests of a substantial proportion of landholders in the two regions. Private landholders recognise how management of this weed on their own properties poses a collective action problem, where success is dependent on the diligent control efforts of neighbouring private and public landholders. They are more likely to consider issues relating to horizontal social capital (e.g. relationships with public and private neighbours) as barriers to effective serrated tussock control on their own property, than issues relating to information and education about this species. Community-based approaches to this weed have the potential to improve its management across the landscape, and a great majority of private landholders appear willing to participate in such a program. Such an approach will require the active participation of public land managers, continued coercion of non-cooperative landholders, and can be developed from the foundation of existing institutional arrangements for land management, taking into account unique regional relationships and characteristics. It should complement and build on, rather than replace existing legislative, research, and extension approaches.